Spousal overprotection is indirectly associated with poorer dietary adherence for patients with type 2 diabetes via diabetes distress when active engagement is low. (8th May 2014) - Johnson, Matthew D.; Anderson, Jared R.; Walker, Ann; Wilcox, Allison; Lewis, Virginia L.; Robbins, David C.
<x xml:space="preserve">Abstract</x> Objectives The current study sought to explore the indirect association of spousal overprotection on patient dietary adherence through the mechanism of diabetes distress and whether the link between overprotection and diabetes distress was moderated by spouse active engagement. Method Participants were 117 married couples in which one member had been diagnosed with type 2 diabetes and were recruited from a patient registry at a Midwestern (USA) medical centre. Data were gathered from spouses and patients through a self‐report survey instrument. The research questions were answered with structural equation modelling using the latent moderated structural equations (LMS) approach and dyadic data analytic procedures. Results Overprotection was associated with reduced dietary adherence indirectly via increased diabetes distress only at low levels of active engagement. The proposed model also proved superior when compared to two plausible alternatives. Conclusions These findings highlight the importance of understanding the nuanced associations among the different ways spouses cope with illness to achieve better diabetes outcomes and the mechanisms responsible for linking coping and dietary adherence. <boxed-text content-type="box" id="bjhp12105-blkfxd-0001" position="anchor" orientation="portrait"> Statement of contribution What is already known on this subject? Spousal coping behaviour can influence dietary adherence among patients diagnosed with type 2 diabetes, positively and negatively. Spouses simultaneously engage in different ways of coping with partner illness, but little is known about the interactive nature of coping styles or possible mechanisms that might link coping with illness outcomes. What does this study add? Spousal overprotection is only associated with reduced patient dietary adherence when spouses are also engaging in low levels of active engagement. Diabetes distress is an important mechanism linking spousal coping with patient dietary adherence. </boxed-text>